Development of Problem-Based Learning-Oriented Student Worksheet to Improve High Order Thinking Skills in Magnet Material in Elementary Schools - Putri Rahayu; Nadia Kurnia Ningsih; Abi Krisna Arrasyid (Program Doktor Pendidikan FKIP Universitas Lampung, 2025)
This study aims to develop a Problem-Based Learning-oriented worksheet to improve students' higher-order thinking skills in magnetics at elementary school. The research subjects were 23 fourth-grade students at SDIT Pelita Khoirul Ummah. The development stages used the ADDIE model, which consists of five steps: analyze, design, development, implementation, and evaluation. The research data types used were quantitative and qualitative. This product was tested using a Likert scale scoring system. The data analysis technique for product effectiveness used the N-gain score, with a pre-test score of 71.04 in the high category and a post-test score of 88.39 in the high category. The conclusion of this research on the development of Problem-Based Learning-based worksheets in elementary schools is that they are suitable for use in improving the higher-order thinking skills of fourth-grade elementary school students.